2006
DOI: 10.1007/s10895-006-0127-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of Styryl Dyes-DNA Complexes Induced by Single- and Two-Photon Excitation

Abstract: The series of novel monomer and homodimer styryl dyes based on (p-dimethylaminostyryl) benzothiazolium residues were synthesized and studied as possible fluorescent probes for nucleic acids detection. Spectral-luminescent and spectral-photometric properties of obtained dyes in the unbound state and in DNA presence were studied. Fluorescence emission induced by two-photon excitation of dye-DNA complexes in aqueous buffer solution was registered. Two-photon absorption cross section values of the studied dyes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…The donor-π bridge-acceptor (D-π-A) structure also promoted intramolecular charge transfer (ICT) fluorescent probes with large Stokes shifts [22]. It was reported that the presence of charged quaternary nitrogen containing ammonium in dye molecule could significantly increase its affinity to the negatively charged nucleic acid [23]. In this work, two new fluorescent probes (1a-b) with D-π-A constitutional feature are designed.…”
Section: Design and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The donor-π bridge-acceptor (D-π-A) structure also promoted intramolecular charge transfer (ICT) fluorescent probes with large Stokes shifts [22]. It was reported that the presence of charged quaternary nitrogen containing ammonium in dye molecule could significantly increase its affinity to the negatively charged nucleic acid [23]. In this work, two new fluorescent probes (1a-b) with D-π-A constitutional feature are designed.…”
Section: Design and Synthesismentioning
confidence: 99%
“…Compound 3 were prepared by 2-methylbenzoxazole and 3-bromopropyl(triethyl)ammonium bromide [23]. The aldehyde 2a can be obtained by a Wittig reaction according to reported methods [24].…”
Section: Design and Synthesismentioning
confidence: 99%
“…[1,2] To date, various organic molecular probes whose fluorescence signals can be significantly enhanced once binding to DNA are widely studied. [3,4] Nowadays, optical microscopy imaging with fluorescent probe has become a new technique for early diagnosis and cancer therapy due to its high selectivity and high resolution. [5,6] Consequently, new molecular probe development for sensitive cell imaging would hold potential application for disease therapy by fluorescence bioimaging.…”
Section: Introductionmentioning
confidence: 99%
“…In our preliminary studies we have shown that Styryl-9M is particularly sensitive to its local environment under 2-photon hyperspectral conditions [22], which is related to the fact that this chromophore possesses a large change of the permanent electric dipole moment between the ground and the first excited state, Δμ = 25 D [23]. In addition, the Styryl dyes are known to be biocompatible [24,25] and so make a good starting point for developing 2-photon imaging agents for use in the tissue transparency region. Most diagnostic methods are not sensitive enough to detect the minimum diagnostically relevant number of malignant cells in tissues.…”
Section: Introductionmentioning
confidence: 99%